Ibn Taymiyyaâs Fatwas on Polygamy in Medieval Islam - Nasir, Mohamad Abdun (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2008)
The paper discusses about the fatwa of Ibn Taymiyya on polygamy. It is well known that as one of the famous jurisconsults in the end of the thirteenth century, Ibn Taymiyya has dispensed many of his responses to Islamic legal cases arose in his time. This paper shows that although relatively an infrequent case posed to him, the issue of polygamy was discussed in such a great length in his book Majmuâ Fatawa. That is why it is important according to the author to know why and what kind of problems related to the practice of polygamous marriage posed to this giant Muslim jurist. It is argued that Ibn Taymiyya tended not to view the practice of polygamy as a wrongdoing although it might lead to some negative excess in concern of its practice in Muslim society. Thus, in spite of some problems that might occur, such as injustice to women, neglecting or deserting to the wives, he does not invalidate the marriage as long as the husband can assure the fairness in distributing material supports. Beyond its substantive legal response, the fatwa of polygamy indicates the rareness of the cases arose in his time. This is true if compared to other problems, such as divorce, pervasively posed to Ibn Taymiyya for a response.